Synthesis And Characterizaition Of Biscyclic β - Lactams As Blood Cholestrol Inhibitors - Salman, Wisam Obaid (University of Thi-Qar Journal of Science, 2014)
This study is concerned with the synthesis and characterization of the 3-(4-chlorophenyl) bicyclic azetidin -2-one 3a. This compound 3a was prepared by reacting 3-(4-chlorophenyl) acetic acid with the appropriate Schiff’s base 2a in the presence of triethylamine with phosphorusoxychloride in dry dichloromethane under nitrogen atmosphere at -10˚C. The active acid chloride reacts with triethylamine to generate corresponding ketene in situ which further reacts with Schiff’s base to furnish corresponding 3-(4-chloroPhenyl)bicyclic azetidin 2–ones 3a.And it was a study of the activity biological to compound 3a to inhibition of cholesterol in the blood of some laboratory animals.